PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PERAN GIZI SEIMBANG DENGAN KOMPOSISI ISI PIRINGKU PADA MASA PANDEMI COVID-19 - Anjar Briliannita; Merinta Sada; Mustika A Matto (LP2M Universitas Hasanuddin, 2022)
In Sorong city, West Papua Province shows that the results of laboratory tests for covid-19 in November 2020, there were an additional 25 positive Covid-19 people, 19 people from Sorong City, and six people from Manokwari Regency. Total positive cases covid-19 in West Papua increased to 4,640 people or 17,3% of the total number of people who had been examined, as many as 26,813. Balanced nutrition is a good step for people in Klamono Village, Klawana Village, to find out how to improve the immune system and prevent contracting Covid-19. This community service aims to increase public knowledge about the role of balanced nutrition during the Covid-19 pandemic. The subjects of this community service are adults and the elderly, as many as 30 people aged between 20 - 51 years. The methods used in this community service are lecture, observation, and documentation. The results of this community service showed that the percentage of previous participants 'knowledge was 55,32%. Furthermore, the post-test results showed that the participants' knowledge had increased to 100%. They understood balanced nutrition with the composition of the contents of my plate as a form of prevention of Covid-19—positive response from participants in the discussion. Nutrition balanced with the contents of my plate is a substitute for four healthy five perfect, which is very easy to understand and apply by participants in their daily life. Consuming balanced nutritious food and drinks with the composition of the contents of my plate will help maintain the body and improve the body's immune system during the Covid-19 pandemic. ... Di Kota Sorong, Provinsi Papua Barat menunjukkan bahwa hasil pemeriksaan laboratorium covid-19 pada bulan november tahun 2020, terdapat penambahan 25 orang positif covid-19 , yang berasal dari Kota Sorong 19 orang, dan Kabupaten Manokwari 6 orang, total kasus positif covid-19 di Papua Barat bertambah menjadi 4.640 orang atau 17,3% dari total jumlah orang yang telah diperiksa sebanyak 26.813 orang. Gizi seimbang merupakan langkah baik bagi masyarakat di Kelurahan Klamono, Kampung Klawana untuk mengetahui cara meningkatkan sistim imun dan pencegahan tertular covid-19. Pengabmas ini bertujuan untuk mengetahui peningkatan pengetahuan masyarakat tentang peran gizi seimbang pada masa pandemi covid-19. Subjek pada pengabmas ini adalah orang dewasa dan lansia, sebanyak 30 orang, berusia antara 20 - 51 tahun. Metode yang digunakan pada pengabmas ini adalah metode ceramah menggunakan power point, dan diberikan pre–post test kepada peserta, serta dokumentasi. Hasil pengabmas ini menunjukkan bahwa presentase pengetahuan peserta sebelumnya sebesar 55,32% dan hasil post test menunjukkan bahwa pengetahuan peserta meningkat menjadi 100% setelah diberikan ceramah, peserta telah memahami gizi seimbang dengan komposisi isi piringku. Respon positif dari peserta dengan adanya pertanyaan dan diskusi. Gizi seimbang dengan isi piringku merupakan pengganti 4 sehat lima sempurna, yang sangat mudah dipahami dan diterapkan oleh peserta dalam kehidupan sehari-hari. Mengonsumsi makanan dan minuman bergizi seimbang dengan komposisi isi piringku akan membantu menjaga tubuh dan meningkatkan sistim imunitas tubuh pada masa pandemi covid-19.